Oxidative stress and its related epigenetic modifications in vascular calcification: mechanisms and advances - Lin, Yanxia; Zhang, Huanrui; Jiang, Yuqi; Tian, Wen (Frontiers in Cardiovascular Medicine, 2025)
Vascular calcification (VC) refers to the pathological deposition of hydroxyapatite within the arterial wall and is characterized by the transdifferentiation of vascular smooth muscle cells (VSMCs) into osteogenic phenotypes. Emerging evidence indicates that oxidative stress plays a pivotal role in the initiation and progression of vascular calcification. Excessive production of reactive oxygen species (ROS) not only activates the expression of calcification-related genes but also promotes VSMC phenotypic switching through diverse epigenetic mechanisms. In this review, we summarize current advances in understanding the interplay between oxidative stress and epigenetic regulation in VC, to provide novel theoretical perspectives on the pathogenesis of this complex vascular disorder.